Motor control of the trunk during a modified clean and jerk lift - Eriksson Crommert, M.; Ekblom, M. M.; Thorstensson, A. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The purpose of the present study was to investigate the pattern of trunk muscle activation and intra-abdominal pressure (IAP) in a somewhat modified version of the clean and jerk lift. Nine healthy physically active male amateurs performed the exercise with a 30-kg barbell. Muscle activity was registered with electromyography from transversus abdominis (TrA) and obliquus internus (OI) using intramuscular electrodes and from rectus abdominis (RA) and erector spinae (ES) with surface electrodes. IAP was recorded with a nasogastric catheter. Measurements were made in various static positions throughout the lift and in the transitional phases separating them, both during lifting and lowering. The results demonstrated that the innermost abdominal muscle, TrA, showed increased activation levels in the two highest positions, whereas ES was most active, together with the highest IAP, in the lowest position. OI and RA showed generally little activation and no obvious trend throughout the lift. The results strengthen the view of a contributing role of TrA to the upright control of the trunk and indicate that the clean and jerk lift might constitute a whole-body exercise, still targeting the TrA muscle, in late-stage rehabilitation, especially for athletes during return to sports.